miRNAs regulating gene expression/gene networks and its multifactorial pathways in open‐angle glaucoma - Blasco, Irene Andrés; Raga‐Cervera, Jorge; Bolarin, Jose M.; Gallego‐Martinez, Alex; Sánchez, Javier Benítez‐Del‐Castillo; Pinazo‐Durán, Maria D.; Zanón‐Moreno, Vicente (Acta ophthalmologica (Oxford, England), 2022)
Purpose: To describe the microRNAs (miRNAs) involved in ocular hypertension (OHT) and open‐angle glaucoma (OAG) to develop miRNA‐based glaucoma diagnostic and therapeutic tools. Methods: An analytical, observational, case–control study was performed in 42 volunteers of both sexes, aged 50 to 80 years, that were classified according to: suffering OHT (n = 20) or with the diagnosis of OAG (n = 20). All participants were interviewed for obtaining sociodemographic and personal/familial records, ophthalmologically examined, and their tear samples were collected and frozen at 80 °C until processing for molecular‐genetic assays. Tear RNA extraction, libraries construction, and next generation sequencing were performed. In addition, Gene information was set up from the DIANA‐TarBase v7, DIANA‐microT‐CDS, and TargetScan v7.1 databases. To build a network of metabolic pathways, only genes appearing in at least four of the following databases: DisGeNet, GeneDistiller, MalaCards, OMIM PCAN, UniProt, and GO were considered. Results: Mean age of participants was 61.1 ± 2.4 years (OHT subjects) and 64.5 ± 1.4 years (OAG patients). In this work we have investigated the delivering of intact miRNAs to target tissues by analysing the tear samples. We identified 95 miRNAs in tears of the OHT subjects and/or OAG patients. When comparing tears from both study groups, the differential expression profiling of eight miRNAs: miR‐26b‐5p, miR‐152‐3p, miR‐30 e‐5p, miR‐125b‐2‐5p, miR‐224‐5p, miR‐151a‐3p, miR‐1307‐3p, and miR‐27a‐3p was found. Also, the interaction networks of the above miRNAS were identified in HTO versus OAG. Conclusions: We propose specific miRNAs and their target genes/signalling pathways as candidates for a better understanding of the molecular‐genetic bases of OAG.